2022
DOI: 10.1021/acsami.2c04743
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Origin of Enhanced Activity of the Nb2O5/H2O2 System in the Elimination of Ciprofloxacin: Insights into the Role of Reactive Oxygen Species in Interface Processes

Abstract: The overlooked role of reactive oxygen species (ROS), formed and stabilized on the surface of Nb2O5 after H2O2 treatment, was investigated in the adsorption and degradation of ciprofloxacin (CIP), a model antibiotic. The contribution of ROS to the elimination of CIP was assessed by using different niobia-based materials in which ROS were formed in situ or ex situ. The formation of ROS was confirmed by electron paramagnetic resonance (EPR) and Raman spectroscopy. The modification of the niobia surface charge by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 40 publications
(79 reference statements)
0
6
0
Order By: Relevance
“…306, 285, 263, 147, confirming successful degradation of the antibiotic. After 6 h of the reaction, the most intense peak occurred at m/z = 263 and was assigned to the CIP molecule in which the piperazine moiety is degraded (see Table 2 ) 41 . It is important to stress that the intensity of the most intense m/z peak, after such a long reaction time, was ca.…”
Section: Resultsmentioning
confidence: 99%
“…306, 285, 263, 147, confirming successful degradation of the antibiotic. After 6 h of the reaction, the most intense peak occurred at m/z = 263 and was assigned to the CIP molecule in which the piperazine moiety is degraded (see Table 2 ) 41 . It is important to stress that the intensity of the most intense m/z peak, after such a long reaction time, was ca.…”
Section: Resultsmentioning
confidence: 99%
“…The flat-band potential ( E fb ) of 0.61 eV could be obtained from the plot of C 2– versus potentials. Therefore, the top of the VB (the highest occupied molecular orbital, HOMO) was determined to be 0.81 eV, and the bottom of the CB (the lowest vacant molecular orbital, LUMO) was calculated to be −1.57 eV. Meanwhile, a photoelectrochemical-transient photocurrent response test of the prepared FeV 3 O 8 nanorods is displayed in Figure d. The i – t plots were recorded with the light on and off every 100 s up to 800 s, for which it can be seen that the anodic potential enhanced sharply under laser irradiation and disappeared quickly when the light source was switched off, which are attributed to the fast charge-carrier transfer and separation rate of the 1D structure FeV 3 O 8 catalyst under light excitation. , …”
Section: Resultsmentioning
confidence: 99%
“…However, Prado et al [15] showed that generating hydroxyl and superoxide radicals. Since the greatest e ciency of this reaction is observed under acidic conditions (pH ∼3) [41], the potential of the Nb 2 O 5 incorporated into the 6% HP gel with an average pH of 6.0-6.5 may not have been fully observed.…”
Section: Discussionmentioning
confidence: 99%